City by city : dispatches from the American metropolis - Gessen, Keith; Squibb, Stephen (New York : n + 1/FARRAR, Straus and Giroux, 2015)
"A collection of essays--historical and personal--about the present and future of American cities Edited by Keith Gessen and Stephen Squibb, City by City is a collection of essays--historical, personal, and somewhere in between--about the present and future of American cities. It sweeps from Gold Rush, Alaska, to Miami, Florida, encompassing cities large and small, growing and failing. These essays look closely at the forces--gentrification, underemployment, politics, culture, and crime--that shape urban life. They also tell the stories of citizens whose fortunes have risen or fallen with those of the cities they call home. A cross between Hunter S. Thompson, Studs Terkel, and the Great Depression-era WPA guides to each state in the Union, City by City carries this project of American storytelling up to the days of our own Great Recession"--
"A collection of essays--historical and personal--about the present and future of American cities"--
Introduction / Keith Gessen and Stephen Squibb -- Welcome to San Diego / Jordan Kisner -- Los Angeles plays itself / Dayna Tortorici -- Modern Fresno / Michael Thomsen -- Bankrupt in Seattle / Jenny Hendrix -- Gold rush Whittier / Erin Sheehy -- The office and the city / Nikil Saval -- The making of local Boise / Ryann Liebenthal -- My Las Vegas / Katy Lederer -- Phoenix rising / Emily Gogolak -- Crossing El Paso / Debbie Nathan -- Upstream in Williston / Nicky Tiso -- Lessons of the Arkansas / Ben Merriman -- Dallas and the Park Cities / Annie Julia Wyman -- The kindness of strangers in New Orleans / Moira Donegan -- M., northern Kentucky / Gary Percesepe -- Six houses in Hyde Park / Sam Biederman -- Milwaukee's gilded age and aftermath / Greg Afinogenov -- Saving Detroit / Simone Landon -- The Cleveland model / interview with Gar Alperovitz -- Neighborhoods of Cincinnati / James Pogue -- Five jobs in Reading / Chris Reitz -- Late show Philadelphia, 1952 / Chanelle Benz -- The highway and the city / Dan Albert -- Atlanta's BeltLine meets the voters / Alex Sayf Cummings -- Dire straits / Michelle Tea -- Fear and aggression in Palm Coast / Elias Rodriques -- Miami party boom / Emily Witt -- Lehigh Acres, designated place / Spencer Fleury -- Disappearing in Duluth / Shawn Wen -- Whit Oak denim, Greensboro / Aaron Lake Smith -- Washington, D.C., brothel / Michael Merriam -- Christmas in Baltimore / Lawrence Jackson -- Philly school reform / Jesse Montgomery -- Bed-Stuy / Brandon Harris -- Providence, you're looking good / Ian MacDougall -- Boston buys resistance / interview with Steve Meacham -- DestiNY Syracuse, USA / Steve Featherstone.
Includes bibliographical references and index.
Keywords: Cities and towns -- United States -- History